Hollow Connecting Rod Thin Wall Austempered Ductile Iron (TWADI) for Manufacturing Light Weight Components - Silva, Ricardina Freitas da; Suharno, Bambang; Sulamet-Ariobimo, Rianti Dewi (UI Scholars Hub, 2024)
Efforts made by the automotive industry to reduce energy consumption have encouraged researchers to carry out various studies. One way is to make components lighter by casting thin wall austempered ductile iron (TWADI). Reducing the weight of components such as connecting rods (conrod) will result in lower energy consumption, but provided that these components still meet standards in terms of mechanical properties and microstructure or even exceed them. In this research, design optimization was applied to conrod by making the area I-beam zero mm (hollow), with hope that it can replace conrod Vespa PX-150. While the manufacturing process is divided into several stages. The focus of this research only discusses the design process stage to determine the optimal design with the help of simulation. The difference is found in the number of defects formed. The observations show that shrinkage defects in Model A and Model B are both located at rod big end. Comparison results of the shrinkage defects formed show that in Model A there are 3 shrinkage defects while in Model B there are only 2 defects. From the results obtained, it is recommended to use plates I-Beam in Model B. Based on the results of this simulation, the casting process can be done to validate the simulation results before optimization is carried out in manufacturing of hollow conrod.